Social Science Perspectives in Early Christian Studies in a Nordic Context - Moxnes, Halvor 1944- (2018)
This homage to Bruce Malina describes his visit to Norway in 1986, and reviews Nordic scholarship using social science criticism in New Testament and Early Christian studies in the last 40 years. Based on a common history and collaboration in academic politics, the Nordic countries make up a unity that has made it possible to establish Nordic studies in Early Christianity as a central player in international scholarship. Nordic scholars have especially been active in the second phase of social science criticism with its focus on social identities and ritual. Their most significant contribution has been in the exploration of socio-cognitive perspectives, where Helsinki University has had a leading role. A major discussion has been the relation between social-science criticism emphasizing the difference between antiquity and the modern world, and cognitive studies that focus on similarity. However, instead of absolute contrasts they may be regarded as supplementary approaches in historical studies of Early Christianity.
Keywords: Nordic context; social-science criticism; socio-cognitive perspectives